Approaches to Indonesia Cultural Tourism Policy - Syah, Ahmad Mujafar; Hajarrahmah, Dini (E-Journal of Tourism, 2019)
In support to the initiative of Indonesia government on the priority destinations project (ten new Bali) where Mandalika in Lombok Island is being endorsed as one of “New Bali” targeted development destination, the research is aimed to analyze the effective roles of national and regional government on the development of cultural tourism destination in Bayan Village, North Lombok administrative region, as it is one of the alternative tourist attractions in Lombok Island. For the purpose of objectivity, this research has limited the source and scope of the observation only from related stakeholders and Lombok local tourism government thus the research employed an in-depth interview through designated stakeholders clusters. The research examined and summarized the finding from the stakeholders’ perspectives that have either direct or indirect concerns toward Bayan Village’s development from which; a proposed recommendation on a tourism policy framework for the cultural destination was concluded. Based on our finding, the situation where the development initiated both by national and regional tourism government in Lombok did not show a fair distribution to all promising destinations especially Bayan Village in North Lombok as one of the cultural tourism assets in North Lombok. Keywords: Cultural tourism destination, cultural tourism governance, tourism policy, stakeholder perspectives.